The impact of direct correction on selective errors on EFL learners writing accuracy performance and attitudes = - Trần, Thị Lệ Huyền (Can Tho University, 2009)
The study aims to find out the impact of direct correction on selective errors on students accuracy performance in writing, the impact of direct correction on selective errors on students attitudes, and the correlation between students accuracy performance and their attitudes.